Exercise Education in Carpal Tunnel Syndrom in Village Kasang Kumpeh - Indah Permata Sari; Mawaddah Warahmah (Asian Journal of Community Services, 2022)
Education exercise on case carpal tunnel syndrome Her workout includes rest wrist hand which painful, avoid profession which  cause painful, compress cold in area which painful During 10-15 minute and practice stretching. This method of education provides leaflet and explain leaflet and discussing exercise education with carpal tunnel syndrome sufferers. Service activities to Public held month October 2021 with target patients with carpal tunnel syndrome in Kasang Kumpeh village. The purpose of activity devotion Public this is for increase public knowledge regarding carpal tunnel syndrome. This activity is very beneficial and also has a good impact on the community to reduce stiffness and complaints pain and for those who only feel the signs and symptoms is very helpful because it gives knowledge to prevent more further occurrence of carpal tunnel syndrome.